United in Diversity, Divided in Adversity? Support for Right-Wing Eurosceptic Parties in the Face of Threat Differs Across Nations - Vergani, Matteo; Bliuc, Ana-Maria; Stuart, Avelie; Badea, Constantina; Muntele, Daniela; McGarty, Craig (Frontiers in Psychology, 2019)
This article investigates whether the perceived threat of terrorism explains the support for right-wing Eurosceptic parties and Euroscepticism above and beyond other relevant variables, including perceived economic and immigration threats. We first examined the entire Eurobarometer samples of 2014 and 2015, and then conducted survey experiments in four European Union (EU) countries, that is, United Kingdom (N = 197), France (N = 164), Italy (N = 312), and Romania (N = 144). Our findings suggest that the perceived threat of terrorism has a small effect on the negative attitudes toward the EU above and beyond the effect of immigration and economic threats and other basic control variables. The relationship between these variables varies across countries and it is less linear than we might expect.